2016
DOI: 10.1371/journal.pntd.0004617
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Chemical Scaffolds Inhibiting Trypanothione Synthetase from Pathogenic Trypanosomatids

Abstract: BackgroundThe search for novel chemical entities targeting essential and parasite-specific pathways is considered a priority for neglected diseases such as trypanosomiasis and leishmaniasis. The thiol-dependent redox metabolism of trypanosomatids relies on bis-glutathionylspermidine [trypanothione, T(SH)2], a low molecular mass cosubstrate absent in the host. In pathogenic trypanosomatids, a single enzyme, trypanothione synthetase (TryS), catalyzes trypanothione biosynthesis, which is indispensable for parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 69 publications
(120 reference statements)
1
72
1
Order By: Relevance
“…For example, 5-aryl-4-benzoyl-3-hydroxy-1-(2-arylethyl)-2 H -pyrrol-2-ones have been identified as competitive and specific vasopressin-2 receptor (V2R) antagonists [54]. Certain 4-aroyl-3-hydroxy-5-phenyl-1 H -pyrrol-2(5 H )-one derivatives showed specificity for targeting trypanothione synthetase in Leishmania infantum [55]. Previously, a series of 4-aroyl-3-hydroxy-5-phenyl-1 H -pyrrol-2(5 H )-ones were reported as inhibitors of the annexin A2–S100A10 protein interaction [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, 5-aryl-4-benzoyl-3-hydroxy-1-(2-arylethyl)-2 H -pyrrol-2-ones have been identified as competitive and specific vasopressin-2 receptor (V2R) antagonists [54]. Certain 4-aroyl-3-hydroxy-5-phenyl-1 H -pyrrol-2(5 H )-one derivatives showed specificity for targeting trypanothione synthetase in Leishmania infantum [55]. Previously, a series of 4-aroyl-3-hydroxy-5-phenyl-1 H -pyrrol-2(5 H )-ones were reported as inhibitors of the annexin A2–S100A10 protein interaction [34].…”
Section: Discussionmentioning
confidence: 99%
“…33 Moreover, previous studies involving paullones as anti-TryS scaffolds revealed that substitution of 4-azapaullones in position 9 or 11 with alkyl or aryl groups is detrimental for target inhibition 34 , whereas paullones harboring a methyl ethylendiamine side chain at the N(5)-position (e.g., 2) inhibited both recombinant L. infantum TryS (LiTryS) and the in vitro growth of L. infantum promastigotes (insect stage). 19,20 The most potent derivative (IC 50 0.15 lM and EC 50 12 lM), containing halogen substituents in position 3 (chloro) and 9 (bromo), produced a significant depletion of trypanothione in L. infantum, which confirmed its on-target effect. 19,20 We here report an approach to develop new paullones with potent growth inhibitory activity against the infective form of T. brucei.…”
Section: Introductionmentioning
confidence: 72%
“…19,20 The most potent derivative (IC 50 0.15 lM and EC 50 12 lM), containing halogen substituents in position 3 (chloro) and 9 (bromo), produced a significant depletion of trypanothione in L. infantum, which confirmed its on-target effect. 19,20 We here report an approach to develop new paullones with potent growth inhibitory activity against the infective form of T. brucei. The new compounds were also screened for their anti-TryS activity against the enzyme from three major pathogenic species of trypanosomatids: T. brucei, T. cruzi and L. infantum.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations